Illegal trafficking conditions of wildlife animals in a rescue center in Guayaquil city - Richards, Romina (2021)
The aim of the study was to identify the species affected by the illegal trafficking of wildlife received in a rescue center in the city of Guayaquil. For this, the records from 2018 to 2020 were collected, from which data were obtained on the origin of the rescue, the presence of injuries and their severity, and the percentage of mortality. Additionally, with the identification of the specimen, it was categorized according to the species, and its situation according to the red list of threatened species of the IUCN (International Union for the Conservation of Nature) and the red books of Ecuador. A total of 743 animals of different species were registered, the juvenile stage being the most frequent. These animals were received by confiscation and voluntary surrender. During this period there was a 10% mortality, with mammals showing the highest rate. According to the IUCN, most of the specimens are in the category of Least Concern, and according to the red books of Ecuador, birds and mammals were located in those of Least Concern and reptiles were registered Vulnerable in a higher proportion.